Multiple Cerebral, Calcified and Infected Hydatid Cysts Case Report and Literature Review - Kisito, Kouassi Jean Marie Quenum; Laghmari, M; Gana, R; Maaqili, MR; Bellakhdar, F (Journal of Neurological Research And Therapy, 2015)
Calcified and Infected Hydatid Cysts Case Report and Literature Review